The Transformation Of Human Resource Management In The Web3 Era: Bibliometric Analysis - Nicky Aprillio; Yossinomita Yossinomita; Ayu Feranika (UNIVERSITAS PAKUAN, 2025)
. This study aims to explore the transformation of human resource management in the Web3 era through a bibliometric analysis of global research trends. The research investigates how decentralized technologies, such as blockchain, smart contracts, tokenization, and Decentralized Autonomous Organizations (DAO) reshape human resource management practices toward transparency, autonomy, and efficiency. Using a descriptive qualitative approach combined with bibliometric analysis, data were collected from the Scopus database (2020–2025) and analyzed using VOSviewer to map keyword networks, identify clusters, and determine research evolution. The findings reveal four major research clusters focusing on blockchain applications, human resource analytics, organizational transformation, and smart contract implementation. Results indicate a paradigm shift in human resource management from administrative functions to strategic, technology-driven roles emphasizing digital competence and data transparency. Moreover, the study highlights challenges in privacy, data regulation, and digital literacy as critical barriers to Web3 adoption in human resource systems. The research provides conceptual insights and a framework for understanding human resource management digital evolution, offering implications for policymakers and organizations to design adaptive, decentralized, and human-centered human resource management strategies.